Lymphoma-associated hemophagocytic lymphohistiocytosis - Marcondes, Thomas de Souza Patto [UNESP]; Chiattone, Carlos Sérgio; Gaiolla, Rafael Dezen [UNESP] (Elsevier, 2025)
Hemophagocytic lymphohistiocytosis is a severe, rare condition characterized by excessive immune activation, leading to significant morbidity and mortality. Lymphoma is the most common trigger for malignancy-related hemophagocytic lymphohistiocytosis in adults, with large B-cell non-Hodgkin, T- and NK-cell lymphomas being the most diagnosed. Hodgkin lymphoma is less frequently observed. Lymphoma-associated hemophagocytic lymphohistiocytosis poses diagnostic and therapeutic challenges due to its complex pathogenesis and heterogeneous presentation. Treatment aims to control the overactive immune system, identify and treat modifying factors, optimize clinical support, and treat the underlying lymphoma. Early etoposide (Etoposide) combined with dexamethasone for immunomodulation results in rapid control of hyperinflammation and clinical improvement. It has increasingly been adopted as a standard initial approach followed by lymphoma-specific treatment. However, the outcomes for patients with lymphoma-associated hemophagocytic lymphohistiocytosis remain poor, especially for patients with T- and NK-cell lymphomas. In relapsed or refractory cases, emerging therapies have been explored, with ruxolitinib showing the most promising results. This paper reviews current understanding of the epidemiology, pathogenesis, clinical features, diagnosis, and treatment of lymphoma-associated hemophagocytic lymphohistiocytosis in adults and proposes an appropriate treatment protocol based on the most recent data from the literature.